Hepatitis B virus mutations, expression quantitative trait loci for PTPN12, and their interactions in hepatocellular carcinoma. (14th April 2016) - Song, Ci; Liu, Yao; Xu, Lu; Wen, Juan; Jiang, Deke; Chen, Jianguo; Zhai, Xiangjun; Hu, Zhibin; Liu, Li; Liu, Jibin
Abstract: Previously we identified that HBV(Hepatitis B virus) sequence variation, which may interact with host human leukocyte antigen ( HLA ) genetic variation, could influence host risk of hepatocellular carcinoma (HCC). More HBV‐host interactions need to be identified. Protein tyrosine phosphatase nonreceptor type 12 (PTPN12), serves as an antagonist to tyrosine kinase signaling, may play integral roles in immune response against HBV infection and the development of HCC. Rs11485985 was an expression quantitative trait loci (eQTL) for PTPN12 by bioinformatics analyses. In this study, we genotyped the PTPN12 eQTL and sequenced the HBV region EnhII/BCP/PC in a case–control cohort including 1507 HBV‐related HCC cases and 1560 HBV persistent carriers as controls. The variant genotype GG of rs11489585 increased HCC risk compared to the HBV persistent carriers (adjusted OR = 2.03, 95% confidence interval [CIs] = 1.30–3.18). We also detected borderline significant associations of PTPN12 eQTL rs11489585 with HBV mutations ( P  = 0.05 for G1799C). Taken together, PTPN12 may influence HCC risk accompanied by HBV mutations. Abstract : PTPN12 may influence HCC risk accompanied by HBV mutations.